Hijrah Instan dan Gaya Hidup Aqidah Populer - Hajrah Ul Jannah; Adelia Putri Cahyani; Hatiti; Adil; Muhammad Parhun (KASTA : Jurnal Ilmu Sosial, Agama, Budaya dan Terapan, 2025)
The phenomenon of instant hijrah has become a trend among young Muslim generations, particularly in the era of social media. Hijrah, which is essentially a deep spiritual process, is now often understood superficially as a change in outward appearance or participation in religious communities without a strong foundation in creed (?aq?dah). This shift is largely influenced by environmental factors, public figures, and social pressures that turn hijrah into a symbol of instant religious status. This context, the so-called popular creed lifestyle has also emerged, referring to the practice and understanding of Islamic values framed within pop culture trends and the commodification of religion. Islamic preaching through digital media, the use of branded modest fashion, and the viral spread of Islamic jargon without deeper meaning are all part of this dynamic. While this lifestyle influences how individuals express their religiosity, it often becomes trapped in symbolism rather than genuine spiritual transformation. This study aims to critically analyze how instant hijrah and the popular creed lifestyle influence the religious patterns of urban Muslim communities. Using sociological and theological approaches, the findings reveal that although these phenomena have the potential to positively spread Islamic values, there is a pressing need to reinforce a deeper understanding of ?aq?dah to prevent religion from becoming mere external identity. A critical awareness in undergoing hijrah and practicing faith is essential to preserve the sincerity of intention and spiritual quality in living a truly religious life.